IDENTIFIKASI FRAUD HEXAGON THEORY DAN PARTISIPASI MASYARAKAT DESA DALAM MEMITIGASI RISIKO FRAUD PENGELOLAAN DANA DESA - Rismayani, Gista; Sukmana, Wawan; Somantri, Yeni Fitriani; Sundari, Yona Rida; Suhaya, Virdha Firdaus; Suganda, Fahmi Fauzan (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
This study aims to identify the impact of pressure, rationalization, and potential collusion on the risk of fraud in managing village funds, where the main obstacles faced are the lack of community participation and low human resources. Community participation is considered an essential form of transparency and accountability in managing village funds in the hope of preventing fraud. This research is a quantitative study designed in the form of a survey. The research population includes villages in the Cibalong Sub-district area, and the area sampling technique of six villages was used. This research used the Structural Equation Modeling Partial Least Squares (SEM PLS) method. The results showed that the elements in the fraud hexagon model, such as pressure, rationalization, and potential collusion, did not significantly impact the risk of fraud in managing village funds. In addition, the findings also show that community participation does not have a significant effect in reducing the likelihood of fraud in the management of village funds. The implications of this research encourage an improved understanding of village fund management practices to reduce the risk of fraud and increase village community participation.